2019
DOI: 10.1088/1742-6596/1382/1/012162
|View full text |Cite
|
Sign up to set email alerts
|

Formation of nanostructures on the surface of KTP single crystals by argon cluster ion beam

Abstract: In this work, the surface of potassium titanyl phosphate (KTP) single crystals has been processed by argon cluster ions having low energy per atom E/Nmean = 12.5 eV/atom. The formation of periodic nanostructures has been studied using atomic force microscopy (AFM) and the power spectral density (PSD) functions. To evaluate the processing efficiency, the dependence of the etching rate of KTP on the incident angles of cluster ions has been investigated. It is shown that the average etching rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It was believed that the Y monotonously falls with increasing angle [38]. However, at least for materials such as SiO 2 , KTiOPO 4 [31] and LiNbO 3 it is now known that this dependence has a pronounced maximum at non-zero angles. Thus, at high fluences (Fig.…”
Section: Sputtering Yieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was believed that the Y monotonously falls with increasing angle [38]. However, at least for materials such as SiO 2 , KTiOPO 4 [31] and LiNbO 3 it is now known that this dependence has a pronounced maximum at non-zero angles. Thus, at high fluences (Fig.…”
Section: Sputtering Yieldsmentioning
confidence: 99%
“…Recently, studies using a single crystal of potassium titanyl phosphate (KTiOPO 4 , KTP) [31,32] have shown that ripples occur in a low-energy irradiation mode (12.5 eV/atom) and do not occur at an energy of 110 eV/atom. The work of Yamada et al [33] demonstrated the growth of ripples arising on SiO 2 film on silicon, with an increase in fluence.…”
Section: Introductionmentioning
confidence: 99%